DEVELOPMENT AND APPLICATION OF SYNTHETIC PROTOCOLS FOR THE GENERATION OF HETEROCYCLIC COMPOUND LIBRARIES - Todorovic, Nikola (My University, 2012)
The development of parallel syntheses that allow for rapid access to compound libraries is widely sought after in drug development and in the study of biological systems. These compound collections can be screened for biological activity and thereby provide useful structure-activity relationships (SAR) to help better understand the biological systems under investigation. This present thesis uses a small molecule library/SAR approach to probe a variety of biological problems such as: inhibiting the proliferation of breast cancer stem cells; inhibiting glutamine fructose-6-phosphate amidotransferase (GFAT, a key enzyme involved in Type II diabetes); and inhibiting aminoglycoside phosphotransferases (APHs, enzymes prevalent in antibiotic resistance). Specifically, synthetic protocols for the parallel preparation of libraries of 3-aryl-pyrimido[5,4-e][1,2,4]triazine-5,7-(1H,6H)-diones, 1-alkyl-3-aryl-1H-pyrazolo[3,4-d]pyrimidin-4-amines, 6-amino-1-alkyl-3-aryl-1H-pyrazolo[3,4-d]pyrimidin-4(5H)-ones, substituted 3-(4-chlorophenyl)-1-(-1H-1,2,3-triazol-4-yl)-1H-pyrazolo[3,4-d]pyrimidin-4-amines and substituted isoquinolines are described. In all cases, a robust synthetic approach was developed allowing for the generation of a library of heterocycles based on hit compounds from high throughput screening. The SARs gained from the assaying of the libraries generated are shown to help in the furthering of the biological understanding of each system.
Keywords: Compound libraries; Isoquinolines; Pyrazolopyrimidines; Toxoflavin; Palladium-catalyzed cross-coupling; Microwave-assisted heating; Organic Chemistry; Organic Chemistry